ANALYSIS OF THE EFFECTS OF WAITING TIME FOR MEDICATION DISPENSING AND SERVICE QUALITY ON PATIENT LOYALTY WITH PATIENT SATISFACTION AS A MEDIATOR AT THE PHARMACY DEPARTMENT OF SANJIWANI GENERAL HOSPITAL GIANYAR - Ni Gusti Ayu Made Sinta Maharani; Rahayu Puji Suci; Eka Wilda Faida; Adya Hermawati; Survival Survival (Journal of World Future Medicine, Health and Nursing, 2026)
The acceleration of globalization compels hospitals to enhance patient loyalty through high-quality services. This study aims to analyze the effect of prescription waiting time and service quality on patient loyalty mediated by patient satisfaction at the Outpatient Pharmacy Department of RSUD Sanjiwani Gianyar. This research design is an explanatory quantitative study rooted in the positivistic paradigm with a developmental research approach. The population comprised all outpatients, averaging 7,836 visits over a six month baseline. A sample of 381 respondents was selected using a non probability purposive sampling technique. Data were collected via structured questionnaires and analyzed using Variance-Based Structural Equation Modeling (SEM) via SmartPLS 4.0. The structural path analysis revealed that waiting time had no significant effect on patient satisfaction or patient loyalty thus, the mediating role of satisfaction on this path was rejected . Conversely, service quality exerted an exceptionally strong, positive, and significant effect on patient satisfaction and directly driven patient loyalty . Furthermore, patient satisfaction significantly and strongly mediated the relationship between service quality and loyalty. Establishing a partial mediation model. The empathy dimension emerged as the primary catalyst that psychologically buffered technical waiting time deficits. Hospital management should heavily focus on emotional care and interpersonal staff interactions to secure sustainable, long-term patient loyalty.